Intergroup empathy: Enhanced neural resonance for ingroup facial emotion in a shared neural production-perception network - Krautheim, Johannes T.; Dannlowski, Udo; Steines, Miriam; Neziroğlu, Gizem; Acosta, Henriette; Sommer, Jens; Straube, Benjamin; Kircher, Tilo (NeuroImage (Orlando, Fla.), 2019)
Empathic behavior and related neural processing are strongly modified by group membership. Shared neural circuits for the production and perception of facial emotional expressions represent mirror neuron mechanisms which play a pivotal role for empathy. In this study, we investigate the influence of group membership on mirror neuron mechanisms for emotional facial expressions. In a functional magnetic resonance imaging task, 178 healthy subjects perceived emotional and neutral facial expressions of artificial ingroup and outgroup members, displayed as 5 s video clips, and produced these facial expressions themselves. Before scanning, artificial group membership was manipulated ad-hoc through a minimal group paradigm. Shared neural activity for emotional facial expression production and perception was revealed in a large network with right-hemispheric preponderance encompassing motor mirror neuron regions, i.e., inferior frontal gyrus, supplementary motor area and middle temporal gyrus, in addition to limbic regions, i.e., amygdala, hippocampus, para-hippocampus, and insula. Within this network there was greater neural activation for ingroup compared to outgroup members in temporal poles, amygdalae, the left insula, the left inferior frontal gyrus, and the inferior and middle temporal gyrus, the right hippocampus and parahippocampus. We validate and extend knowledge on brain regions with mirror neuron properties. Most crucially, we provide evidence for the influence of group membership on regions within the mirror neuron system, indicating more neural resonance (mirroring) for ingroup facial emotional expressions. •There is enhanced neural resonance (mirroring) for ingroup facial emotions.•Such ingroup bias affects amygdala, temporal pole, and hippocampus activation.•Ad-hoc created minimal group membership sufficiently induces this ingroup bias.•Knowledge about brain regions with mirror neuron properties is extended.